Synthesis of 2,3,5,6-tetra-O-benzyl-D-galactofuranose for α-glycosidation - Gola, G. (2006)
The synthesis of 2,3,5,6-tetra-O-benzyl-D-galactofuranose, a useful compound for α-glycosylation studies, is described. Direct anomeric O-alkylation of galactose was employed for alpha-allylation to yield pure allyl α-D-galactofuranoside, which is a versatile precursor for the synthesis of galactofuranose-containing oligosaccharides. Allyl removal of the benzylated galactofuranosyl derivative was performed using palladium (II) chloride as catalyst. ©ARKAT.